Serangga pengunjung bunga tumbuhan liar dan potensinya untuk mendukung penyerbukan jambu mete (Anacardium occidentale L): Flower-insect visitors on wild plants and its potential to enhance pollination on cashew (Anacardium occidentale L) - Supriyadi, Supriyadi; Wijayanti, Retno; Arniputri, Retna Bandriyati; Azizin, Fakhriza Nikma (Jurnal Entomologi Indonesia, 2023)
Pollination is important in cashew production, thus it is important to understand the factor determining the presence of pollination in cashew habitat. The research was carried out by field surveys in cashew farms to record the insects that exhibited nectar and pollen foraging activities on wild and cashew flowers. This study recorded the similarity between flower-insect visitors on wild plants and cashews, namely families of Apidae, Halictidae, Pieridae, and Andrenidae. Apidae were the most important flower visitors, but the honey bee, Apis sp. as an important pollinator, did not show the highest abundance. Wild flowering plants in cashew fields have the potential to play a role in the conservation of cashew pollinators.